(untitled) - Thomsett, Michael C. (Hoboken, N.J., 2005)
Just as location is a critical component to the value of real estate, knowledge is a critical component to investing success. As with any type of new endeavor, gaining knowledge and experience is essential as you move forward toward success. If you're interested in generating rental income through an investment in real estate, but unsure of how to go about doing this, Getting Started in Rental Income will show you the way. Written in a straightforward and accessible manner, this book discusses the two major ways of entering the rental income market--the traditional purchase of rental properties or buying and selling fixer-upper properties--and reveals what you need to do once you're in.
Keywords: Real estate investment,Rental housing,Đầu tư bất động sản,Giá thuê nhà ở